Negotiating gender justice, contesting discrimination mapping strategies that intersect culture, women and human rights - Mehra, Madhu; Sharma, Gayatri (Partners for Law in Development, 2010)
This report documents diverse strategies adopted by community groups in Bangladesh, India, Indonesia and Nepal to negotiate women's rights in the context of culture, while grounding the strategies in the specific political - historic local and national contexts. It looks at secular strategies along with the more recent responses to fundamentalism, that use of cultural identity and religious/cultural resources. These admittedly political strategies that use cultural resources seek to contest not just sex discrimination, but also the orthodox, elite, male monopoly of cultural leadership. The report provides a rich account initiatives that promote culture as relational, transforming, plural and accommodating of women's rights, and in doing so, challenge dominant static and fundamentalist assertions of culture.